IMPLEMENTASI KOMPETENSI KEPRIBADIAN GURU DALAM PEMBELAJARAN DI TK NEGERI PEMBINA PONTIANAK BARAT - Rena, Rena; Fadillah, Fadillah; Syukri, Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to find out about the implementation of the teacher's personal competence in learning at TK Negeri Pembina Pontianak Barat. The research method used was qualitative. The subjects in this study were 6 teachers at TK Negeri Pembina Pontianak Barat. Data collection techniques used was direct observation techniques, direct communication techniques and documentary techniques with data the collection tools observation and interview guides also documentation. The results obtained that the implementation of teacher personality competencies in learning at TK Negeri Pembina Pontianak Barat can be carried out well as follows, 5 of 6 teachers can implemented the teacher personality competencies that are steady and stable in learning, by fostering discipline to students, all teachers can implemented a mature personality that is not emotion in dealing with problems, not all teachers can implemented a wise personality in learning, there was still 1 teacher who does not carry out her responsibilities as a teacher, all teachers have implemented an authoritative personality in learning of students by providing a good example to students, all teachers have implemented a personality that has a noble character to students by being honest.Key words: Early Childhood Learning, Teacher’s Personal Competence